Analyzing Research Trends on High Intensity Interval Training and Oxidative Stress: A Bibliometric Analysis (2003-2024) - Meena, Anshul; Chahar, Pradeep Singh; Singh, Jagdeep (Physical Education Theory and Methodology, 2025)
Background. Exercise-induced oxidative stress, often resulting from high-intensity interval training (HIIT), can cause short-term declines in performance due to alterations in cellular and DNA function. Therefore, oxidative stress markers have gained increased attention for their potential role in reducing risks and improving individual performance. Objectives. This study aimed to assist researchers and practitioners in grasping current research trends and exploring future research directions in the field of oxidative stress and HIIT. Materials and methods. This paper presents a comprehensive bibliometric overview and visualization of research on oxidative stress in HIIT, analyzing 192 publications from the Scopus database. Scopus was chosen for data extraction due to its prominence as Elsevier’s citation database, high-quality peer-reviewed works, and four metrics: h-index, CiteScore, SCImago Journal Rank (SJR), and Source Normalized Impact per Paper (SNIP). Results. By employing various visualization tools to analyse influential authors, organisations, and keywords, the paper identifies leading publications and key research clusters related to oxidative stress in HIIT. Conclusions. Through performing citation and reference co-citation analyses, the study highlights central research topics and emerging trends pertaining to oxidative stress in HIIT.